2017
DOI: 10.11606/issn.2316-9079.v16i1p57-62
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Boana albopunctata (Anura: Hylidae) in an Atlantic Forest fragment of southeastern Brazil

Abstract: Anurans are important in trophic food chains because they feed on invertebrates, many of which are harmful to humans. We investigated the diet of 100 specimens of Boana albopunctata from an Atlantic Forest fragment in Ponte Nova municipality, Minas Gerais state. We obtained 107 prey items. The most common prey were Lepidoptera, Araneae and Coleoptera. This species tended to select larger prey in smaller quantities as found in previous reports, but differed in the taxons selected because of spatial and temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Amphibians play important roles in the food webs of ecosystems because they represent a link between terrestrial and aquatic environments [2,3]. The diet of anurans is generally based on arthropods [4] and is influenced by factors such as prey availability [5,6], habitat changes [7], body size [8][9][10], seasonality [11,12], hunting strategy [13][14][15][16] and evolutionary factors [17]. Although anurans' diet consists basically of insects [1], it can also include vertebrates, as bats [18,19], fishes [20], snakes [21] and other anurans [batracophagy: 14,[22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amphibians play important roles in the food webs of ecosystems because they represent a link between terrestrial and aquatic environments [2,3]. The diet of anurans is generally based on arthropods [4] and is influenced by factors such as prey availability [5,6], habitat changes [7], body size [8][9][10], seasonality [11,12], hunting strategy [13][14][15][16] and evolutionary factors [17]. Although anurans' diet consists basically of insects [1], it can also include vertebrates, as bats [18,19], fishes [20], snakes [21] and other anurans [batracophagy: 14,[22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…In this sense, reports on the natural history and diet of anurans emphasize the importance of conducting studies in different habitats to understand the feeding patterns of widely distributed species [6], such as L. podicipinus. In the Pantanal of Miranda, the diet of L. podicipinus essentially consisted of invertebrates, particularly of Coleoptera.…”
mentioning
confidence: 99%
“…Most diet studies usually identify prey to the ordina eve e o and dder atista et , Oliveira et al 2017, Pacheco et al 2017; probably this is because the food items are found at an advanced stage of digestion. We were able to identify most (78.5%) prey at the familial level.…”
Section: Dietmentioning
confidence: 99%
“…Hunting tactics can vary among anurans, ranging from those who hunt by lurking to those who actively search for prey (Duellman and Trueb, 1994). In addition, other factors, such as the nutritional value of prey (Lima et al, 2010), coexistence with other species (Pacheco et al, 2017; Sant'Anna et al, 2022), the occupation of the micro-habitat (Van Sluys and Rocha, 1998), their physiology, morphology, and natural history (Blanco-Torres et al, 2017), may influence the diet of anurans.…”
Section: Introductionmentioning
confidence: 99%